Botulinum Toxin A: Dose-dependent Effect on Reepithelialization and Angiogenesis. Issue 8 (August 2016) - Gugerell, Alfred; Kober, Johanna; Schmid, Melanie; Buchberger, Elisabeth; Kamolz, Lars-Peter; Keck, Maike
Abstract : Background: Botulinum (neuro)toxin A (BoNT) is widely used in the field of plastic and reconstructive surgery. Among treatment of pain, hyperhidrosis, or aesthetic purposes, it is also used to enhance wound healing and prevent excessive scar formation. Some clinical data already exist, but only little is known on a cellular level. The aim of this study was to evaluate the effect of BoNT on cells essential for wound healing in vitro. Therefore, primary human keratinocytes and endothelial cells were treated with different concentrations of BoNT and tested on proliferation, migration, and angiogenic behavior. Methods: BoNT was exposed to human keratinocytes and endothelial cells in a low (1 IU/mL), medium (10 IU/mL), and high (20 IU/mL) concentrations in cell culture. Proliferation and migration of the 2 cell types were observed and also the angiogenic potential of endothelial cells in vitro. Results: BoNT 20 IU/mL negatively influenced proliferation and migration of keratinocytes but not those of endothelial cells. Angiogenesis in vitro was less effective with the highest BoNT concentrations tested. Low concentrations of BoNT supported sprouting of endothelial cells. Conclusions: High concentrations of botulinum toxin interfered with wound closure as keratinocytes' proliferation and migration were deteriorated. Furthermore, BoNT concentrations of 20 IU/mL constrain in vitro vessel formation but do not influence proliferation or migration of endothelial cells.